The study of the mathematics, information technology and physics in the faculty of pedagogy: the analysis of attitudes - Tamošiūnas, Teodoras (Lietuvos matematikos rinkinys, 2000)
The paper investigates the expert evaluation of four study subjects, provided by 131 primary school teachers, 201 graduate students of the Faculty of Education and 117 tutors of the Faculty of Education. Didactic of Mathematics takes up 6 position, Information Technology – 34, Mathematics – 46, Physic – 72 position in the row of 74 study subjects in the Faculty of Pedagogy. Research data analysis has been performed by methods of mathematical statistics. It is presented 4 conclusions.